Peningkatan Kemampuan Merangkum Teks Laporan Hasil Observasi Menggunakan Model Pembelajaran Cooperative Integrated Reading and Composition (Circ) Siswa SMP Aksara Bajeng Kabupaten Gowa - Anin Asnidar; Nurhasanah Hasyim (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research was motivated by the results of the ability to summarize the contents of the text of the results of observations of class VII A Bajeng Script Middle School. This study aims to find out (1) The implementation of learning summarizes the contents of the text of the observation report using the CIRC learning model (2) Improving the ability of learning outcomes in summarizing the text of the observation report using the CIRC learning model in class VII A SMP Aksara Bajeng. This research is classroom action research which consists of two cycles. The subjects of this study were all students of class VII A with a total of 25 students. The treatment given to research subjects to improve learning outcomes of the material summarizes the contents of the text of the observation report using the CIRC learning model. The results showed that the implementation of learning using the CIRC learning model was appropriate to improve students' abilities in summarizing the text of the observation report. This is evidenced by the value of student learning outcomes that have increased each cycle. In the initial test the average value of students was 47.92 with a learning mastery level of 28%. In cycle I the average value of student learning was 62.4 with a mastery level of 44%. Cycle II student average score of 81.8 with a mastery level of 80%. Based on the research results above, it can be concluded that the learning outcomes of class VII A students at Bajeng Script Middle School through the application of the Cooperative Integrated Reading and Composition learning model have increased.